Black Rice (Oryza sativa L., Poaceae) Extract Reduces Hippocampal Neuronal Cell Death Induced by Transient Global Cerebral Ischemia in Mice - Hwang, Sun-Nyoung (Exp Neurobiol, 2018)
Rice is the most commonly consumed grain in the world. Black rice has been suggested to contain various bioactive compounds including anthocyanin antioxidants. There is currently little information about the nutritional benefits of black rice on brain pathology. Here, we investigated the effects of black rice (Oryza sativa L., Poaceae) extract (BRE) on the hippocampal neuronal damage induced by ischemic insult. BRE (300 mg/kg) was orally administered to adult male C57BL/6 mice once a day for 21 days. Bilateral common carotid artery occlusion (BCCAO) was performed for 23 min on the 8th day of BRE or vehicle administration. Histological analyses conducted on the 22nd day of BRE or vehicle administration revealed that administering BRE profoundly attenuated neuronal cell death, inhibited reactive astrogliosis, and prevented loss of glutathione peroxidase expression in the hippocampus when compared to vehicle treatment. In addition, BRE considerably ameliorated BCCAO-induced memory impairment on the Morris water maze test from the 15th day to the 22nd day of BRE or vehicle administration. These results indicate that chronic administration of BRE is potentially beneficial in cerebral ischemia.